(untitled) (Journal of the College of Basic Education, 2023)
Unsaturated CdO and iron samples were synthesized with 5 wt% iron by spray pyrolysis method. The optical properties of the samples were studied in the spectral range (300-900) nm. Doping increases the optical transmittance of CdO and reduces the optical band gap (eg) from 2.49 eV to 2.46 eV. The extinction coefficient (K0), absorption coefficient (α), skin depth (γ), refractive index (n), photoconductivity, and dielectric constants were calculated and related to the doping.